2014
DOI: 10.1007/s11010-014-2121-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-125a inhibits porcine preadipocytes differentiation by targeting ERRα

Abstract: MicroRNAs are a family of small, non-coding RNAs that regulate gene expression in a sequence-specific manner. Estrogen-related receptor α (ERRα) is an orphan nuclear receptor which plays an important role in adipocyte differentiation. Our previous Solexa sequencing results indicated a high expression of miR-125a in adult pig backfat. In this study, we predicated and experimentally validated ERRα as a target of miR-125a. To explore the role of miR-125a in porcine preadipocytes differentiation, miRNA agomir and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Accumulating evidence suggests that miR-125a plays an important role during adipogenesis 15 16 . Importantly, Ras homolog family member A (RhoA), a small GTPase that plays key roles in adipogenesis, has been reported as a target gene of miR-125a-3p 17 .…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that miR-125a plays an important role during adipogenesis 15 16 . Importantly, Ras homolog family member A (RhoA), a small GTPase that plays key roles in adipogenesis, has been reported as a target gene of miR-125a-3p 17 .…”
mentioning
confidence: 99%
“…miRNA-125a EXPRESSION miR-125a directly regulates ERRa gene expression through binding site locates at ERRa 3 0 UTR [Ji et al, 2014]. Since our RNA-seq gene expression profiling also showed that curcumin increased miR-125a level ( Supplementary Table SI).…”
Section: Curcumin Inhibits Erra Expression By Upregulatingmentioning
confidence: 63%
“…The adipogenesis in porcine cell culture is shown in two steps: the recruitment of lipid-free preadipocytes and the stimulation of lipid growth in the recruited preadipocytes. Studies carried out on this cell line showed that phloretin enhances the lipid accumulation in a time-dependent manner [78], retinol-binding protein 4 (RBP-4) suppresses differentiation in porcine preadipocytes by decreasing the activation of insulin and that miR-125a promotes the differentiation of porcine preadipocytes upon inhibition [79]. In contrast, miR-199a promotes cell proliferation while attenuating the lipid deposition in porcine adipocytes.…”
Section: Animal Cell Modelsmentioning
confidence: 99%